2012
DOI: 10.1007/s13277-012-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

PAK1-dependent MAPK pathway activation is required for colorectal cancer cell proliferation

Abstract: P21-activated protein kinase1 (PAK1), a main downstream effector of small Rho GTPases, Rac1, and Cdc42, plays an important role in the regulation of cell morphogenesis, motility, mitosis, and angiogenesis. Despite its importance, the molecular mechanisms of PAK1 that contributed to colorectal carcinogenesis remain unclear. Our immunohistochemistry showed that PAK1 expression was increased with colorectal cancer (CRC) progression through the adenoma to carcinoma sequence. Furthermore, our results suggested a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…Additionally, it was investigated if PAK1 knockdown and 5-FU synergistically inhibits tumour growth in a xenograft model. LoVo cells harbouring shPAK1 constructs were injected into nude mice and PAK1 knockdown significantly reduced tumour growth and proliferation 91. A further reduction in tumour growth was observed in combination with 5-FU.…”
Section: Pharmaceutical Modulation Of Pak1mentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it was investigated if PAK1 knockdown and 5-FU synergistically inhibits tumour growth in a xenograft model. LoVo cells harbouring shPAK1 constructs were injected into nude mice and PAK1 knockdown significantly reduced tumour growth and proliferation 91. A further reduction in tumour growth was observed in combination with 5-FU.…”
Section: Pharmaceutical Modulation Of Pak1mentioning
confidence: 99%
“…PAK activation affects NF-κB,16 87 MAPK,8991 PI3K92 and Wnt/β-catenin signalling13 linking inflammation and malignant transformation in the gut. Further, PAK signalling promotes epithelial–mesenchymal transition and invasiveness,1 3 93 both of which are common features of colitis-associated cancer (CAC).…”
Section: Paks In Gi Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our findings suggested that PAK1 plays a critical role in the proliferation of squamous-cell carcinomas. Several different downstream pathways have been shown to mediate oncogenic signaling related to PAK1 [19,20], but it is not clear which pathways regulate the progression of lung cancer. Recently, PAK4, a group-II PAK family member, was shown to promote prostate cancer progression through CREB [10].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%